Using Lotus Notes as an intranet. - Falkner, Mike, 1954- (New York, United States of America : John Wiley & Sons, Inc., 1997)
On the CD-ROM you'll find: 25 Lotus Notes Databases for use with the Notes/Domino™ server technology. Great Plains® Dynamics accounting software with Notes integration.
Consult book 004.6 F191
Keywords: LOTUS NOTES FOR WINDOWS -- CD-ROM; LOTUS DOMINO -- CD-ROM; INTRANETS -- COMPUTER NETWORKS -- CD-ROM; LOTUS NOTES -- COMPUTER PROGRAM -- CD-ROM